Misi Gereja Katolik Bagi Konsep Ketuhanan Suku Tetun Nai Maromak Refleksi Analisis Misi bagi Fenomena Budaya - Mali, Alfrid (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2022)
This paper raises the concept of the Godhead of the Tetun tribe as reflected by the mission of the Catholic Church. The concept of Nai Maromak in the culture of the Tetun tribe, which is very animistic, has become the concept of divinity in the Catholic Church, which leads to Jesus Christ. The concept of the Godhead of the Tetun tribe has fundamental similarities with the concept of the Godhead of the Catholic Church. With the mission of the Church up to the cultural life of the Tetun tribe, it can bring together and direct the teachings of the Church on the concept of God. The animist concept of Nai Maromak was brought into contact with the mission of the Church to the concept of God that is recognized by the world in the Catholic Church. The process of this paper is more directed to a reflection on the analysis of the mission of the Church for the cultural phenomenon of the Tetun tribe, especially regarding the concept of God. This reflection of the analysis of the Church’s mission describes the concept of divinity in a culture that is reflected in the view of the teachings of the Catholic Church so that we can find an inculturative concept of divinity. The results of this analytical reflection are very helpful for Tetun people in living the faith of the Church, especially Jesus is Nai Maromak. Abstrak Tulisan ini mengangkat mengenai Konsep Ketuhanan suku Tetun yang direfleksi oleh misi Gereja Katolik. Konsep Nai Maromak dalam budaya suku Tetun yang sangat animisme menjadi konsep ketuhanan dalam Gereja Katolik yakni mengarah kepada Yesus Kristus. Konsep ketuhanan budaya suku Tetun mempunyai kesamaan fundamental dengan konsep Ketuhanan agama Katolik. Dengan adanya misi Gereja Katolik sampai pada kehidupan berbudaya Suku Tetun bisa mempertemukan dan mengarahkan kepada ajaran Gereja Katolik mengenai konsep Ketuhanan. Konsep Nai Maromak yang animisme digiring dalam perjumpaan dengan misi Gereja Katolik kepada Konsep Ketuhanan yang diakui dunia dalam Gereja Katolik. Proses tulisan ini lebih mengarah kepada refleksi analisis Misi Gereja Katolik bagi Fenomena Budaya Suku Tetun khususnya mengenai konsep Ketuhanan. Refleksi analisis misi Gereja ini mengurai tentang konsep ketuhanan dalam budaya yang direfleksikan menurut pandangan ajaran Gereja Katolik, sehingga bisa menemukan konsep ketuhanan yang inkulturatif. Hasil dari refleksi analisis ini sangat membantu orangorang Tetun dalam menghayati iman Gereja Katolik khususnya Yesus adalah Nai Maromak. Kata-kata Kunci: Misi, Nai Maromak, Suku Tetun, Konsep Ketuhanan